National code in contemporary literary criticism: in studies of Zhangarа Dadebay (Eurasian Journal of Philology Science and Education, 2019)
In the article as examples of classic literature reviewed scientific research: Professor J. Dadebaev’s«ТарихиРашидидің әдебиэстетикалық мәні» and «Көне түркі әдеби ескерткіштерінің көркемдікжүйесіндегі жанр түзуші факторлар», which is in the opinion of the author of the first theoreticalanalyses of famous monuments of the Kazakh literature. Literary critic Zh. Dadebaev for the first timecarried out a structural analysis of the known canonical texts. At the same time, the texts themselves aresubjected to a detailed textual analysis, representing the presence of both the author’s and the author’spositions, and the main characters, as well as the artistic and historical basis of the literary heritage.